Discourse analysis of the perceptions of environmental justice and respiratory health disparities in Dallas, TX. Issue 3 (4th March 2022) - Namin, Sima; Ko, Yekang; Zhou, Yuhong; Beyer, Kirsten
ABSTRACT : This article examines the perceived relationships between environmental justice and health disparities among minority populations in the Dallas, TX metropolitan area. We study the varying discourses on EJ and respiratory health disparities, and how the local discourses are different from what is understood by planners and environmental advocates. We also ask how a participatory approach can provide an inclusive platform to strengthen the efforts to reduce health disparities. Utilizing a survey, a focus group of local residents, and in-depth interviews with local government officials, urban planners, environmental and health advocates, and urban ecologists, we identify and discuss key discourses of health disparities and environmental (in) justice to better understand different positionalities. Using Foucauldian discourse analysis, three discursive approaches were identified: "institutional racism", "inclusion and recognition", and "scientific evidence". Drawing on these identified discourses we illustrate the importance of the political and social framings of environmental justice and health concerns and perceptions to better inform community health promotion efforts. The results highlight the importance of incorporating knowledges from various stakeholders in the analysis of environmental inequalities in parallel with the ecological understanding of environmental and human health disparities.